Analysis of Reading Interest of English Education of Students on Scientific Articles - Feby Alifia Fitriyanti; Yuna Tresna Wahyuna; Nina Puspitaloka (Universitas Muhammadiyah Enrekang, 2022)
This study aims to determine how interested students are in reading scientific articles in the English Education Department and to find out what factors make students interested in reading scientific articles in the English Education Department. The research method used in this study is a qualitative research method. The results showed that the reading interest of English education students towards scientific articles was quite good. Reading interest arises from within students because of the demands of academics to achieve educational goals and ideals. The factors that make students interested in reading scientific articles are educational. The lecture material and the completion of final assignments require students to read many references to scientific articles. Then there is the motivation factor, where the motivation comes from the lecturer who always provides support so that students read more scientific articles to increase knowledge and insight and motivation from within because of the demands of lecture material or completion of final assignments to achieve their goals.